Implementasi Pengaruh Inflasi, Suku Bunga, dan CAR Terhadap Profitabilitas Bank Konvensional - Vyonita Anggraeni Ningrum (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to determine the effect of inflation, interest rates, and CAR on the profitability of conventional banks. This study uses four variables, namely inflation, interest rates, and CAR as the dependent variable, and bank profitability as the independent variable. The population in this study are banking sector companies that have been listed on the IDX (Indonesia Stock Exchange) for the period 2015-2019, totaling 43 companies. The data collection method uses purposive sampling using financial reports on conventional banks in Indonesia which are listed on the IDX in the 2015-2019 period. The results show that inflation, interest rates, and CAR simultaneously affect the profitability of conventional banks listed on the IDX for the 2015-2019 period, inflation has no significant effect on ROA, interest rates do not have a significant effect on ROA, and CAR has a significant effect on ROA. Keywords: Inflation; Interest rates; CAR (capital education ratio)